Expert System in Career Exploration Based on Business and Industrial Needs - Armentaria, Jeki (Jurnal Informasi dan Teknologi, 2023)
Era Society 5.0 is the development of technology-based human activities. Rapid technological developments have an impact on human life, one of which can eliminate jobs and can also create new jobs. The Business and Industrial World (DUDI) is one sector that has an impact on technological developments with the hope that the human resources who will work later are superior human resources so that they can innovate well. This study aims to measure the entrepreneurial personality of SMK students using an expert system application. The methodology used in this research is Research and Development (R&D). There are four stages to do: Definition, Design, Development and Dissemination. The instrument used to measure entrepreneurial personality is inventory (non-test) with four indicators of entrepreneurial personality, namely Extroverted, Leader, Moderate Risk Taker, Ambisious, which have undergone a fit test using Confirmatory Factor Analysis. The result of this research is an expert system application that can recommend jobs based on six career-oriented personality types. Based on the results of data analysis, the Entrepreneurship Personality-based career development application was declared valid, practical and effective in measuring the entrepreneurial personality of vocational students in percentage (0.89) and very practical (91.11) and the results of product effectiveness were 82.47 (effective).